Parental appearance teasing in adolescence and associations with eating problems: a systematic review - Dahill, Lucy M. (BMC Public Health, 2021)
BACKGROUND: The adolescent years see significant physical and emotional development that lay foundations for patterns of behaviour that can continue into adult life, including the shaping of eating behaviours. Given parents are key socio-environmental drivers and influencers of adolescent behaviours around physical health and wellbeing, it is critical to consider if specific forms of parental communication are potentially contributing to the associated emotional difficulties experienced in the adolescent years. The aim of this research was to systematically review the myriad of literature pertaining to the prevalence of parental weight or appearance-based teasing and adolescent eating problems to examine how the scientific and clinical community currently understands the relationship between these domains. METHODS: A systematic search of the literature, using the SCOPUS, APA PsycINFO, Medline, CINAHL databases, reference lists and Google Scholar, was undertaken to identify relevant literature for parental teasing and problem eating in adolescents aged 10–19 years, published between January 1980 to October 2020, in English or French. RESULTS: Six studies met criteria for inclusion, all were cross-sectional studies and two included additional prospective data. Although parents were not the most common perpetrators of teasing, often subsidiary to that of peers and siblings, the influence and impact of parental teasing remained significant, and in some cases, appeared to interact with sibling-based teasing. This teasing was associated with problem eating behaviours for adolescents. CONCLUSIONS: There is evidence in the literature to suggest the existence of an association between ‘eating problems’ amongst adolescents and exposure to parental appearance or weight teasing. Parents are unlikely to be aware of the perception or impact of the words they use or the wider influence these words may have. Future research should employ representative longitudinal designs to develop a greater understanding of the relationships between parental communications around their adolescent’s appearance or weight and how that communication is perceived by adolescents within complex family processes. TRIAL REGISTRATION: PROSPERO 2018 CRD42018109623. Prospectively registered 15th October 2018. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10416-5.